Evaluation of a Personal Digital Assistant Device Implementation for Barcode Medication Administration with Nurses Using a Likert Questionnaire - Descalzo, Juan Marcos (2022)
The majority of preventable medication errors occur at the administration stage. BCMA systems are used to improve safety and prevent errors in this stage. A variety of devices can be used for this purpose. Hospital Italiano de Buenos Aires is a high complexity medical center implementing a BCMA project since 2015. It is currently migrating to PDA devices for nurses. The objective of this work is to evaluate the implementation of these new devices in selected wards at HIBA using a self-reported questionnaire. From 318 contacted nurses, 58 answered the questionnaire (18.2% response rate). Overall, agreement was high among all statements regarding the new devices. Nurses valued especially the increased safety to reduce errors, improvements in previous hospital processes and achieving improvements in the flow and quality of patient care. Nurses recommended the use of the device in their sector, with a mean score of 4.6/5 and 91.3% agreement, highest in total. This proved to be a cost-effective method of evaluation of the newly implemented devices and acceptance by nurses. Measures to incorporate the remaining nurses' feedback should be considered.